A highly oriented conductive MOF thin film-based Schottky diode for self-powered light and gas detection - Cao, Lin-An; Yao, Ming-Shui; Jiang, Hui-Jie; Kitagawa, Susumu; Ye, Xiao-Liang; Li, Wen-Hua; Xu, Gang (Journal of materials chemistry. A, Materials for energy and sustainability, 2020)
The application of Schottky junction in self-powered devices is limited by low efficiency in both separation and transport of photogenerated electrons/holes. This issue may be overcome by introducing electronically conductive metal-organic framework (EC-MOF) materials into the junction and limited by preparing high-quality thin films of EC-MOFs. In this study, for the first time, high-quality EC-MOF thin films were demonstrated as effective interlayer materials to solve the above-mentioned issue by modulating the height of Schottky barrier ( Φ B ). The EC-MOF-based self-powered Schottky diode can act as a photodetector and demonstrate the highest external quantum efficiency (84%) for all reported self-powered photodetectors as well as the broadest detectable spectrum range (250 to 1500 nm), high on-off ratio (∼10 3 ) and short rise (0.007 s) and fall time (0.03 s). Furthermore, it can be used as a gas sensor for typical harmful gases and vapors. High-quality EC-MOF thin films are used to modulate the Schottky barrier height and detect light/gas by self-powered mode.